No Role for Mast Cells in Obesity-Related Metabolic Dysregulation - Chmelař, Jindřich; Chatzigeorgiou, Antonios; Chung, Kyoung-Jin; Prucnal, Marta; Voehringer, David; Roers, Axel; Chavakis, Triantafyllos (Frontiers in Immunology, 2016)
Obesity-related adipose tissue (AT) inflammation that promotes metabolic dysregulation is associated with increased AT mast cell numbers. Mast cells are potent inducers of inflammatory responses and could potentially contribute to obesity-induced AT inflammation and metabolic dysregulation. Conflicting findings were reported on obesity-related metabolic dysfunction in mast cell-deficient mice, thus creating a controversy that has not been resolved up to date. Whereas traditional Kit hypomorphic mast cell-deficient strains featured reduced diet-induced obesity and diabetes, a Kit-independent model of mast cell deficiency, Cpa3Cre/+ mice, displayed no alterations in obesity and insulin sensitivity. Herein, we analyzed diet-induced obesity in Mcpt5-Cre R-DTA mice, in which the lack of mast cells is caused by a principle different from mast cell deficiency in Cpa3Cre/+ mice or Kit mutations. We observed no difference between mast cell-deficient and –proficient mice in diet-induced obesity with regards to weight gain, glucose tolerance, insulin resistance, metabolic parameters, hepatic steatosis and AT or liver inflammation. We conclude that mast cells play no essential role in obesity and related pathologies.